Metaphor As A Stylistic Device Based On The Transference Of Meaning (Texas Journal of Multidisciplinary Studies, 2025)
This article explores metaphor as a fundamental stylistic device in language and literature, focusing on its basis in the transference of meaning. Drawing upon linguistic and literary theories, the article analyses the types, structures, and functions of metaphors in English, highlighting their cognitive and stylistic roles. It also reflects on how metaphors serve to enrich expression, structure thought, and reflect cultural values.